Pengaruh Dividen Announcement, Capital Gain dan Kurs Terhadap Trading Volume Activity (Studi Kasus pada Saham Syariah yang Terdaftar di JII Tahun 2015-2018) - Atika, Bella (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
The capital market is a company tool to increase long-term funding needs by selling shares and issuing bonds. A measurement tool for calculating trading volume is trading volume activity (TVA). The purpose of this study is to examine the effect of dividend announcements, capital gains and exchange rates on trading volume activity (TVA) on Islamic stocks listed on JII in 2015 to 2018. This study uses eight Islamic shares, namely ADRO, ASII, INDF, LPFF, PGAS, PTBA, SMRA and UNTR. The data in this study were obtained through an annual report from the IDX website. Based on paired differences test shows that in 2105, 2016 and 2017 there were no significant TVA differences between before and after dividend announcements, whereas in 2018 there were significant TVA differences between before and after dividend announcements. The panel data regression analysis results showed that the capital gain variable has no effect on TVA, while the exchange rate variable has a positive and significant effect on TVA. Keywords:Â Trading Volume Activity, Dividen Announcements, Capital Gain, Kurs